Cerebral Cortical Activity During Academic Stress Amongst Undergraduate Medical Students at Kampala International University (Uganda) - Mujinya, Regan; Kalange, Muhamudu; Ochieng, Juma John; Ninsiima, Herbert Izo; Eze, Ejike Daniel; Afodun, Adam Moyosore; Nabirumbi, Ritah; Sulaiman, Sheu Oluwadare; Kairania, Emmanuel; Echoru, Isaac; Okpanachi, Alfred Omachonu; Matama, Kevin; et al. (Frontiers in Psychiatry, 2022)
Background Stress among medical students is related to their academic lifespan; however, information on brain health among medical students from developing countries continues to be scarce. The objective of this study was to establish perceived academic stress levels, assess the ability to cope with stress, and investigate its effects on the visual reaction time (VRT), audio reaction time (ART), and tactile reaction time (TRT) in the somatosensory cortex among medical students of Uganda. Methods This was a cross-sectional study conducted among preclinical (n = 88) and clinical (n = 96) undergraduate medical students at Kampala International University Western Campus. A standard Perceived Stress Scale (PSS) was used to categorize stress into low, moderate, and severe while the ability to cope with stress was categorized into below average, average, above average, and superior stresscoper (SS). Data on reaction time were acquired through VRT, ART, and TRT using the catch-a-ruler experiment, and this was analyzed using SPSS version 20. Results This study shows that preclinical students are more stressed than clinical students (PSS prevalence for low stress = preclinical; clinical: 40, 60%). Moderate stress was 48.4 and 51.6% while high perceived stress was 75 and 25% among preclinical and clinical students. Among male and female students in preclinical years, higher TRT and VRT were found in clinical students showing that stress affects the tactile and visual cortical areas in the brain, although the VRT scores were only significantly (P = 0.0123) poor in male students than female students in biomedical sciences. Also, highly stressed individuals had higher TRT and ART and low VRT. SS had high VRT and ART and low TRT in preclinical students, demonstrating the importance of the visual cortex in stress plasticity. Multiple regression showed a close relationship between PSS, ability to cope with stress, age, and educational level (P < 0.05), demonstrating the importance of social and psychological support, especially in the biomedical sciences. Conclusion Preclinical students suffer more from stress and are poorer SS than clinical students. This strongly impairs their cortical regions in the brain, thus affecting their academic productivity.